The Samuelson macroeconomic model as a singular linear matrix difference equation - Fernando Ortega; Maria Filomena Barros (Journal of Economic Structures, 2020)
In this paper, we revisit the famous classical Samuelson's multiplier-accelerator model for national economy. We reform this model into a singular discrete time system and study its solutions. The advantage of this study gives a better understanding of the structure of the model and more deep and elegant results.
Keywords: 330; Samuelson; Macroeconomic; Singular; System; Difference equations